The identities of Cancer arenarius Toreen, in Osbeck, 1765, Cancer arenarius Zimmermann, in Cavolini, 1792, Cancer (Mantis) arenarius Herbst, 1793, and Cancer (Gammarellus) arenarius Herbst, 1793, and other names associated with the genus Ocypode Weber, 1795 (Crustacea: Amphipoda, Decapoda, Stomatopoda) - Low, Martyn E. Y.; Ng, Peter K. L. (Zootaxa, 2012)
The binomial name Cancer arenarius has been proposed in five different works for species of Crustacea. The earliestname, Cancer arenarius Toreen, in Osbeck, 1765, is identified with Ocypode ceratophthalmus (Pallas, 1772), with usageof the latter name being maintained by a reversal of precedence. We identify Cancer arenarius Zimmermann, in Cavolini,1792, with Eriphia verrucosa (Forskål, 1775). Cancer (Mantis) arenarius Herbst, 1793, is a preoccupied and unavailableobjective synonym of Lysiosquillina maculata (Fabricius, 1793), and we herein designate the neotype of the latter as thesimultaneous neotype of the former to fix the identities of both names. Cancer (Gammarellus) arenarius Herbst, 1793, isidentified with Gamarellus homari (Fabricius, 1779). Cancer arenarius Catesby, 1771, has been deemed not an availablename by the Zoological Commission, but is identifiable with Ocypode quadrata (Fabricius, 1787). Cancer eques Aubertde la Chesnaye des Bois, 1759, and Ocypoda ippeus Olivier, 1804 (and its incorrect original spelling, Cancer hippeus),are both referred to Ocypode cursor (Linnaeus, 1758), while Ocypoda edwardsi Osorio, 1890, is a subjective juniorsynonym of Ocypode africana De Man, 1881. The authorship of Cancer erythropus (now Dromia erythropus): Edwards, in Catesby, 1771, is also clarified.